Stress Relief and Support for Stability of Deep Mining Roadway with Thick Top Coal in Hujiahe Coal Mine with the Risk of Rock Burst - Wenjing Liu; Deyu Qian; Xingguo Yang; Sujian Wang; Jinping Deng; Qi Cui; Zexiang Li (Shock and Vibration)
Rock burst is a typical dynamic disaster in deep underground coal mining. Based on the support problems of the deep roadways in fully mechanized caving face 401111 of Hujiahe Coal Mine suffering from rock burst in Shaanxi Province of China, the failure law and influencing factors of the surrounding rock of the roadway are analyzed. The results show that the deformation of surrounding rock in the roadway shows the characteristics of elastic, plastic transformation, rheology, and expansion. At the same time, it has the typical characteristics of deep roadway, such as the fast deformation speed, long duration, asymmetric deformation, and large loose broken area of surrounding rock. Based on the principle of “strengthening support in shallow zones” and “deep pressure relief in deep zones” in the surrounding rock, the control scheme of surrounding rock in the return roadway of fully mechanized caving working face 401111 is proposed by taking the large diameter pressure relief and deep hole blasting as the main means of pressure relief. The practice shows that the surrounding rock of the return roadway is relatively stable after the implementation of the new scheme, which shows that the design of the new support scheme is reasonable and reliable. It is of great significance for the stability control of surrounding rock of the mining roadway suffering from rock burst.